Using medicinal plants: impacts and perspectives on nursing care in a rural community - Manuelle Arias Piriz; Marcos Klering Mesquita; Cláudio Tosi Cavada; Josiane Santos Palma; Teila Ceolin; Rita Maria Heck (Universidade Federal de Goias, 2013)
Using medicinal plants is an ancient and multicultural form of treatment. The objective of this study was to rescue popular knowledge regarding medicinal plants used in a rural community in Southern Rio Grande do Sul state, Brazil, and discuss the inclusion of this complementary practice in Primary Care. This qualitative, descriptive and exploratory study was conducted using semi-structure interviews with 20 patients between June and July of 2009. The data were analyzed according to themes. The subjects referred 51 medicinal plants, which were related to the digestive (19 plants), respiratory (13), and endocrinal (8) systems, and to hypertension (7) and treatment of infectious diseases (6). The patients used medicinal plants as a complementary treatment, but do not report to healthcare professionals. For Nursing, particularly in rural areas, the impact from using medicinal plants unveils the need for constant knowledge exchange, from an interdisciplinary perspective, thus strengthening its nucleus of action. Descriptors: Plants, Medicinal; Primary Health Care; Community Health Nursing.